EFEK ANTIINFLAMASI EKSTRAK ETANOL DAUN KAMBOJA (Plumeria rubra L.) PADA TIKUS PUTIH (Rattus norvegicus) - Safriani Rahman; Aulia Wati; Ema Sukmawati (Fakultas Farmasi UMI, 2018)
Inflammation is a body protective response against tissue injury which can be characterizet by the formation of edema. Frangipani Leaves contain flavanoids, saponins and alkaloids. The flavanoid compound is considered to have a useful effect for healing edema. This research aimed to examine the effects of anti-inflamatory and determined the dose of ethanol extract of the frangipani leaves (Plumeria rubra L.) as an anti-inflammatory in the rat. The test of anti-inflammatory effect was done by using the Rat Hind Paw Edema method in which test animals it used 15 rats divided into 5 groups: groups I (negative control) was given Na.CMC 1% w/v, group II (positive control) was given diclofenac sodium, group III, IV and V were given the ethanol extract of the frangipani leaves successive doses of 166,6mg/kgBW, 222,2 mg/kgBW, and 277,7 mg/kgBW, all groups were orally administered. The tested animals were induced carrageenan 1% w/v in intraplantar 0,5 mL and were meansured their foot edema volume before performed before induction as the intial volume (Vo), after induction, and 1 hour after the administration of the dosage form for 5 hours with the intervals of 1 hours using the pletismometer. The research result data were proccessed statistically using on-wey anova. Based of the data analysis showed that the ethanol extract of the frangipani leaves have the activity as the anti-inflammatory and statistically, the assay extract group showed the result not significantly different (p>0,05) against the diclofenac sodium group and a dose of 277,7mg/kgBW possessed the best activity compared to a dose of 166,6mg/kgBW and 222,2mg/kgBW.